Dense gas star formation efficiency and the LHCN (4−3)′/LHCO+(4−3)′ ratio: insights from a statistical study of infrared bright star-forming galaxies - Jiao, Qian; Gao, Yu; Tan, Qinghua; Gao, Yang (Frontiers in Astronomy and Space Sciences, 2023)
We present a statistical study on dense molecular gas tracers of HCN (4–3), HCO+ (4–3) lines and molecular tracers of [C i], and CO observations for a sample of 26 infrared bright star-forming (SF) galaxies. We investigate the dependence of dense gas star formation efficiency traced by HCN (4–3), HCO+ (4–3) (that is LIR/LHCN (4-3)′, and LIR/LHCO+(4−3)′), and luminosity ratio of LHCN (4-3)′/LHCO+(4−3)′ on [C i]-CO ratios of L[C I] (1-0)′/LCO (1-0)′, L[C I] (2-1)′/LCO (1-0)′ and L[C I] (2-1)′/L[C I] (1-0)′ (hereafter R[CI]) which are sensitive to interstellar medium conditions. Our findings show that both LIR/LHCN (4-3)′ and LIR/LHCO+(4−3)′ have moderate correlations with L[C I] (2-1)′/LCO (1-0)′ and R[CI], while LHCN (4-3)′/LHCO+(4−3)′ does not show any significant correlations with any of the [C i]-CO ratios. We compare the LHCN (4-3)′/LHCO+(4−3)′ ratios of AGN and SF galaxies, and find that although the higher LHCN (4-3)′/LHCO+(4−3)′ ratios are mainly found in AGN, the majority of the LHCN (4-3)′/LHCO+(4−3)′ values in SF galaxies are comparable to those in AGN. Based on our findings, it appears that the LHCN (4-3)′/LHCO+(4−3)′ ratio may not be a reliable indicator of the presence of an AGN, although further investigation is needed to confirm this conclusion.